Whole‐exome sequencing identified mutational profile of a case with T‐cell chronic lymphocytic leukemia. Issue 11 (30th July 2020) - Nozaki, Kenji; Yokota, Takafumi; Itotagawa, Eri; Tsutsumi, Kazuhito; Kusakabe, Shinsuke; Morikawa, Yoichiro; Fujita, Jiro; Fukushima, Kentaro; Maeda, Tetsuo; Shibayama, Hirohiko; Hosen, Naoki; Kumanogo, Atsushi; et al.
Abstract: We believe that our report and further case reports on T‐cell chronic lymphocytic leukemia with genetic profile will contribute to the molecular classification of this rare but distinct disease. Abstract : We believe that our report and further case reports on T‐cell chronic lymphocytic leukemia with genetic profile will contribute to the molecular classification of this rare but distinct disease.